An Inherently Masculine Practice: Understanding the Sexual Victimization of Queer Women - Bedera, Nicole (Journal of interpersonal violence, 2021)
Sexual violence is a widespread social issue, and sexual victimization is especially prevalent among queer-identified women. Still, there is little research on queer women’s experiences of sexual violence or explanations for the high rate of victimization. This study uses data from 40 open-ended interviews to investigate queer women’s experiences with sexual violence and those who perpetrate it. Respondents answered questions about the characteristics of their sexual assaults and perpetrators, as well as connections the survivors perceive between their sexual assaults and sexual identities. Findings indicate that the perpetrators of such sexual assaults invoke an expression of masculinity, regardless of the perpetrator’s gender identity at the time of violence. To understand the nuanced role of masculinity in queer assailant’s assaults, we develop the concept of “righteous masculinity,” which refers to a traditional (and, in this case, violent) masculinity invoked by marginalized people in an attempt to reclaim power. We find that sexual violence against queer women is an especially powerful way to enact masculinity through drawing upon misogyny and homophobia simultaneously, providing an explanation for the high rates of sexual victimization among queer women. We argue that centering masculinity can help scholars and activists better challenge the sexual victimization of queer women and deepen understanding of the links between gender-based violence and masculinity.